Mechanical Properties of a “5+4” Viscoelastic Damping Wall Based on Full-Scale Laboratory Tests - Junhong Xu; Aiqun Li (Shock and Vibration)
This paper presented temperature scanning tests of the viscoelastic materials firstly. The temperature scanning tests were carried out by a Rheogel-E4000DMA analyzer and the results showed the modulus and loss factor of viscoelastic damping material. Secondly, the full-scale laboratory test of the “5+4” VDW was carried out. The test was conducted on an electrohydraulic servo tester. A new shear loading mode in the transverse direction was proposed for the VDW. And the maximum damping force, the storage stiffness, the loss stiffness, equivalent damping coefficient, the shear storage modulus, the shear loss modulus, and the loss factor were discussed in the text.